2023
DOI: 10.3390/nano13050946
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Hollow Carbon Spheres Derived from Fullerene Assembly as Electrode Materials for High-Performance Supercapacitors

Abstract: The energy storage performances of supercapacitors are expected to be enhanced by the use of nanostructured hierarchically micro/mesoporous hollow carbon materials based on their ultra-high specific surface areas and rapid diffusion of electrolyte ions through the interconnected channels of their mesoporous structures. In this work, we report the electrochemical supercapacitance properties of hollow carbon spheres prepared by high-temperature carbonization of self-assembled fullerene-ethylenediamine hollow sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…3387.2 m 2 g –1 and 1.963 cm 3 g –1 , respectively. These values are much higher than the commercially available activated carbon materials or other porous carbon materials derived from other synthetic carbon sources including fullerene crystals. K 2 CO 3 also introduces defects or structural irregularities in the carbon lattice, which can function as active sites for electron transfer, further improving the prospects of these materials in energy storage applications.…”
Section: Resultsmentioning
confidence: 99%
“…3387.2 m 2 g –1 and 1.963 cm 3 g –1 , respectively. These values are much higher than the commercially available activated carbon materials or other porous carbon materials derived from other synthetic carbon sources including fullerene crystals. K 2 CO 3 also introduces defects or structural irregularities in the carbon lattice, which can function as active sites for electron transfer, further improving the prospects of these materials in energy storage applications.…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported, the resulting CS had an excellent large surface area (1439.3 m 2 g −1 ) and large pore volume (1.346 cm 3 g −1 ). 32 Due to the lack of hydrophilic groups on the CS surface, CS could not be directly dispersed in water. To address this problem, we added CS to the TC aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…The C 60 -based nanospheres were synthesized as previously reported. 32 A solution of EDA (0.55 mL) in m -xylene (5 mL) was prepared by applying sonication for 30 min. 5 mL of a C 60 solution in m -xylene (1 mg mL −1 ) was then added to the EDA/ m -xylene solution, and the obtained solution was thoroughly mixed on a vortex mixer for 10 s. After 40 min of incubation, the precipitates in the solution were collected by centrifugation at 9500 rpm for 10 min and repeatedly washed with IPA and DI-water 3 times, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Due to their specific structures, high surface areas, and large pore volumes, the assembled supercapacitor delivers a considerable energy density of 37.4 Wh kg –1 at 212 W kg –1 . It is worth noting that hollow porous carbon spheres (HCS) have large specific surface area and superior electrochemical performance attributed to their nanoscaled shell thickness, rich mesoporous structure, and large cavity structure, making them potential materials for the next-generation supercapacitors. Ariga et al reported the electrochemical supercapacitance properties of hollow carbon spheres prepared by high-temperature carbonization of self-assembled fullerene-ethylenediamine hollow spheres (FE-HS), which have enormous potential for electrochemical energy storage supercapacitor applications . Xu et al proposed highly porous, N-doped HCNs (pyrrole and aniline as carbon sources) via the interfacial copolymerization strategy and NH 3 -assisted carbonization for SCs and Li–S batteries .…”
Section: Introductionmentioning
confidence: 99%
“…17−20 Ariga et al reported the electrochemical supercapacitance properties of hollow carbon spheres prepared by high-temperature carbonization of self-assembled fullerene-ethylenediamine hollow spheres (FE-HS), which have enormous potential for electrochemical energy storage supercapacitor applications. 21 Xu et al proposed highly porous, N-doped HCNs (pyrrole and aniline as carbon sources) via the interfacial copolymerization strategy and NH 3 -assisted carbonization for SCs and Li−S batteries. 22 Cai et al reported a supercapacitor with hollow porous nanostructures, in which the modified-SiO 2 nanospheres were used as the template and agar as the carbon resource.…”
Section: ■ Introductionmentioning
confidence: 99%